Association Between Air Temperature and the Incidence of Acute Coronary Heart Disease in Northeast China - Wang X (Dove Medical Press, 2020)
Xue Wang, 1 Yizeng Jiang, 2 Yingzhe Bai, 3 Chao Pan, 2 Renzi Wang, 4 Miao He, 1 Jinghai Zhu 1 1Institute of Environmental and Health, School of Public Health China Medical University, Shenyang, People’s Republic of China; 2Department of Emergency, Horqin District First People’s Hospital of Tongliao, Tongliao, People’s Republic of China; 3Department of Air Detection Information Technology Support Center, Tongliao Meteorological Observation, Tongliao, People’s Republic of China; 4Department of Clinical Medicine, Air Force Medical University, Xian, People’s Republic of ChinaCorrespondence: Jinghai ZhuInstitute of Environmental and Health, School of Public Health China Medical University, Puhe Road 77, Shenyang, Shenbei 110122, People’s Republic of ChinaEmail zhujinghai2019@163.comAim: The aim of this study was to examine the association between air temperature and incidence of acute coronary heart disease in Northeast China.Methods: We obtained coronary heart disease (CHD) daily hospitalization data from January 2017 to June 2019, and collected meteorological data including average daily air temperature, air pressure, relative humidity, wind velocity, sunshine duration and water vapor pressure, for the same period. Totally, This study included data from 6775 patients with CHD.Results: After adjusting for confounding factors, low air temperature was inversely associated with CHD. Additionally, in the warm season (April–September), the number of daily hospital admissions for CHD was higher (≥ 24.2°C) if the average daily air temperature was low (≤ 15.4°C).Conclusion: Low air temperature might be a risk factor for CHD among the elderly, especially in the warm season.Keywords: air temperature, coronary heart disease, elderly, warm season, cold season